An SMFL-based non-destructive quantification method for the localized corrosion cross-sectional area of rebar. (November 2021) - Qiu, Junli; Zhang, Hong; Zhou, Jianting; Zhang, Weiping
Abstract: The non-destructive quantitative evaluation of the rebar corrosion degree is an urgent problem to be solved for corroded reinforced concrete structures. In this study, a non-destructive quantification method for the rebar localized corrosion cross-sectional area was proposed based on the dynamic linkage mechanism of the induced magnetic and self-magnetic flux leakage fields of rebar. As verified by data from the experiment and the finite element simulation, this quantification method could eliminate the adverse influence of the magnetic property differences of the rebar. The results indicated that different quantitative indices for corrosion evaluation could be created based on this method, and an index created by two transformations with the same geometric characteristics had better quantification capability. The four quantitative indices I 1, I 2, I 3, and I 4 created in this study were all linearly related to the rebar localized corrosion cross-sectional area ratio S, and index I 3 had the relatively best quantitative capability and applicability. This quantification method provided an innovative solution for the non-destructive quantitative evaluation of rebar corrosion. Highlights: The dynamic linkage mechanism between the IM and SMFL fields of corroded rebar was demonstrated. An SMFL-based non-destructive quantification method for the rebar corrosion degree was proposed. Four quantitative indices were created based on this quantification method. All of the created quantitative indices were linearly related to the corrosion cross-sectional area of rebar.